2020
DOI: 10.1037/ccp0000616
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of improvements and maintenance in online relationship programs for distressed low-income couples.

Abstract: Objective: Web-based relationship interventions have been shown to improve relationship functioning for low-income couples, with gains maintained up through 12 months (Doss et al., 2020; Roddy et al., 2020). However, little is known about mechanisms of improvements and maintenance for these programs. Method: A sample of 742 low-income couples (Mage = 33; 55% non-Hispanic White; 52% married; Mdn annual household income = $27,000) were randomly assigned to the OurRelationship (OR) program, the ePREP program, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Additionally, it is possible that learning new skills, as well as hearing from other couples’ experiences may contribute to greater hope about the future of the couple relationship (e.g., Hawkins et al, 2017). Our results demonstrate the potential value of couples having dedicated time spent together to focus on their relationship, and these results add to the growing body of scholarship examining factors that contribute to positive couple outcomes (Barton et al, 2017; Cooper et al, 2021; Le et al, 2020).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Additionally, it is possible that learning new skills, as well as hearing from other couples’ experiences may contribute to greater hope about the future of the couple relationship (e.g., Hawkins et al, 2017). Our results demonstrate the potential value of couples having dedicated time spent together to focus on their relationship, and these results add to the growing body of scholarship examining factors that contribute to positive couple outcomes (Barton et al, 2017; Cooper et al, 2021; Le et al, 2020).…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have been mixed about the influence of content mediators, such as changes in communication. Some studies found that changes in communication‐mediated changes in later relationship quality (Barton et al, 2017; Le et al, 2020), while another did not (Williamson et al, 2016). Another study found that participants’ reports of specific tool usage were also not related to improvements in overall relationship satisfaction (Carlson, Guttierrez, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, being able to properly communicate about individual differences so that each partner feels understood, as ePREP teaches, could reduce individuals talking past their partner or reduce the number of vitriolic fights that may occur. Indeed, separate mediation studies in a sample from the same larger study seem to support these conclusions (Le et al, in press). However, it is also possible that other nonspecific changes—such as implicit messages sent by both partners agreeing to do the program—also contributed to these changes.…”
Section: Discussionmentioning
confidence: 94%